MP2RAGE and Susceptibility‐Weighted Imaging in Lesional Epilepsy at 7T. Issue 4 (24th May 2018) - Pittau, Francesca; Baud, Maxime O.; Jorge, João; Xin, Lijing; Grouiller, Frédéric; Iannotti, Giannina R.; Seeck, Margitta; Lazeyras, François; Vulliémoz, Serge; Vargas, Maria Isabel
ABSTRACT: BACKGROUND AND PURPOSE: Surgery is the first choice therapeutic approach in case of drug‐resistant epilepsy. Unfortunately, up to 43% of patients referred for presurgical assessment do not have a lesion detectable by routine 3T magnetic resonance imaging (MRI) (MRI‐negative), although most of them likely have an underlying epileptogenic lesion. Thus, new MRI modalities with increased sensibility for epileptogenic lesions are required. This paper describes the magnetization‐prepared two rapid acquisition gradient echoes (MP2RAGE) and susceptibility‐weighted imaging (SWI) findings at 7T in a series of patients with drug‐resistant epilepsy of different etiologies. METHODS: Prospective pilot study of 7 patients with drug‐resistant lesional epilepsy and absence of contraindications for MRI underwent a research 7T head‐only scanner. Qualitative analysis of the high‐resolution MP2RAGE and SWI sequences is given for each case. This study was approved by the local ethics committee. Written informed consent was obtained from each participant. RESULTS: This study shows that such sequences at ultra‐high field are new and valuable approaches to unravel and characterize epileptogenic lesions. Particularly, MP2RAGE shows a better delineation of lesions due to high gray‐white matter contrast and structural resolution, and SWI reveals new imaging signs related to improved magnitude and phase contrast imaging. CONCLUSION: MRI at ultra‐high field is very promising for the detection of inconspicuous epileptogenic lesions and may facilitate epilepsy surgery of a great number of to‐date MRI‐negative patients.